Meningkatkan Aktivitas Belajar Membaca Menggunakan Teknik Bermain pada Siswa Kelas III SDN 2 Hajimena, Lampung Selatan - Erlis, Dekapi (Lentera: Jurnal Ilmiah Kependidikan, 2022)
The purpose of the study is in line with the formulation of the problem, so this study aims to improve learning activities in Indonesian language reading material through the application of Playing Techniques to Class III students of SD Negeri 2 Hajimena South Lampung. The method used is CAR with planning, implementation, observation and reflection steps carried out in 3 cycles. The research subjects were Class III students of SD Negeri 2 Hajimena South Lampung TP 2019/2020, totaling 34 students. The results showed that the application of the Playing technique could increase the activity of learning Indonesian with reading material for Class III students of SD Negeri 2 Hajimena South Lampung in the 2019/2020 school year.